Mini-Review on Renewable Production of Green p-Xylene - Muchammad, Raka Selaksa Charisma; Saputro, Erwan Adi; Rohmah, Aisyah Alifatul Zahidah (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2024)
The sustainable and renewable production of p-xylene (PX), a crucial component for polyethylene terephthalate (PET), is increasingly important as an alternative to fossil-based processes. This review examines biomass-derived routes for PX synthesis, emphasizing the use of bio-px production pathways to feasible for commercialization. While bio-PX production offers reduced greenhouse gas emissions, challenges remain in cost, catalyst stability, and energy requirements. Recent innovations in catalyst regeneration and hierarchical structures enhance stability and minimize coke formation. Life-cycle assessments confirm bio-PX’s environmental advantages, suggesting that further research into biomass sources and catalyst efficiency will advance bio-based PX production toward commercial viability in a sustainable bioeconomy.